Thinking Beyond the Paradigms: Debunking 10 Myths in Youth - Praveen Parameswar (Notionpress, 2015)
Myths in a circuit form the cultural framework which is essentially an out-and-out model of myth. Terribly deceptive, they become those hurdles in our life which, if we never cross, life comes to a standstill. This book effectively debunks 10 such hard myths for the youth making us realize our prejudiced view of the world, rewriting for us the actual know-how of these myths. Let us learn the truth in the lies we believed in. "Let's be clear..."